Does Early Artificial Rupture of Membranes Speed Labor in Preterm Inductions? - Parrish, Melissa M.; Kuper, Spencer G.; Jauk, Victoria C.; Baalbaki, Sima H.; Tita, Alan T.; Harper, Lorie M. (American Journal of Perinatology, 2018)
Objective In full-term patients, early artificial rupture of membranes (AROMs) decreases time in labor. We assessed the impact of early AROM in preterm patients undergoing indicated induction of labor.Study Design We conducted a retrospective cohort study of all patients undergoing indicated preterm induction (23–34 weeks) at a single tertiary care center from 2011 to 2014. Early AROM was defined as <4 cm and late AROM was defined as ≥4 cm. The primary outcomes evaluated were cesarean delivery and time in labor. Secondary outcomes were chorioamnionitis and a composite of maternal and neonatal adverse outcomes.Results Of the 149 women included, 65 (43.6%) had early AROM. Early AROM was associated with an increased time from the start of induction to delivery (25.7 ± 13.0 vs. 19.0 ± 10.3 hours, p < 0.01) and with an increase in the risk of cesarean (53.4 vs. 22.6%, adjusted odds ratio: 3.5, 95% confidence interval: 1.60–7.74). Early AROM was not associated with an increased risk of chorioamnionitis or adverse maternal or fetal outcomes.Conclusion In this observational cohort, early AROM was associated with an increased risk of cesarean. A randomized controlled trial is necessary to determine the optimal timing of AROM in preterm patients requiring delivery.
Keywords: early amniotomy; preterm; indicated induction of labor